The role of agroforestry tree species in biocontrol of the cabbage pest Plutella xylostella : a field study in Kenya - Kvick Nastaj, Nadja (SLU/Dept. of Ecology, 2020)
Pest control in agriculture is a necessity and the use of chemicals is the method by choice for most farmers. But the use of chemicals comes with a price; the pests develops resistance and the chemicals pollutes the environment. It is therefore of urgent importance to shift pest control from chemicals to other methods. Biological control is an alternative which can prove to be as effective as chemicals but without the negative effects. In Kenya, the agriculture sector is the backbone in the economy, contributing to the livelihood of near 80% of the population. One of the most common vegetables grown in the country is cabbage, but due to various pests, the production is threatened. The most severe pests affecting cabbage is the diamondback moth, Plutella xylostella, DBM for short. If left uncontrolled, the moth larvae can lead to massive yield losses, and in Kenya entire yields have been destroyed. This study aimed to investigate if the use of different tree species used in an agroforestry system affected the presence of two natural enemies to DBM, parasitoids and insectivorous birds. Cabbage plants, Brassica oleracea var. capitate, were grown specifically for the study and distributed to different plots fulfilling specific study criteria regarding presence of one of three tree species. Observations of DBM-larvae presence and collection of pupae were made at regular intervals during a period of two weeks. Due to bad weather conditions during the study: drought during the initial phase leading to plants dying, followed by rainy nights hampering the expected DBM population growth, the DBM abundance was much lower than expected. Due to these circum-stances leading to reduced number of replicates when entire plots had to be abandoned and DBM densities were low, statistical tests of data could not be performed. Nevertheless, caged plants seemed to have an effect, indicating that birds did contribute to the reduction and the loss was slightly higher on Macadamia plots.